2013
DOI: 10.1155/2013/398308
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Revision of Hepatocellular Adenomas: A Learning Experience

Abstract: Light has been shed on the genotype/phenotype correlation in hepatocellular adenoma (HCA) recognizing HNF1α-inactivated HCA (H-HCA), inflammatory HCA (IHCA), and β-catenin-activated HCA (b-HCA). We reviewed retrospectively our surgical HCA series to learn how to recognize the different subtypes histopathologically and how to interpret adequately their immunohistochemical staining. From January 1992 to January 2012, 37 patients underwent surgical resection for HCA in our institution. Nine had H-HCA (25%) charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
3
17
1
Order By: Relevance
“…Recently, Fonseca et al . reported one case of β‐catenin‐activated/HNF1α‐inactivated HCA . Castain et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fonseca et al . reported one case of β‐catenin‐activated/HNF1α‐inactivated HCA . Castain et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fonseca et al reported one case of β-catenin-activated/HNF1αinactivated HCA. 28 Castain et al showed the coexistence of inflammatory HCA with H-HCA in nine cases. 29 In the present study, we carefully differentiated these HCA from HCC using histological and immunohistochemical methods because, in our additional study, we showed the loss of LFABP expression in approximately 10% of HCC, which was closely associated with β-catenin activation (unpubl.…”
Section: W E Distinguished Four Subtypes and Twomentioning
confidence: 99%
“…One phenotype consisted of atypical hepatocytes with microvesicular lipid droplets. Immunohistochemically, these cells did not express liver fatty acid‐binding protein and glutamine synthetase (GS), both of which are found in HNF‐1α‐inactivated hepatocellular adenoma . The second phenotype of liver tumors consisted of atypical hepatocytes with diffuse expression of GS, glypican‐3, alpha‐fetoprotein and nuclear expression of beta‐catenin, thus resembling HCC in humans (Fig.…”
Section: Ms–nash‐hcc Model Micementioning
confidence: 99%
“…Several studies have described the applicability of the L-FABP protein to the detection of hepatic injury in diseases such as hepatocellular adenoma 12 and chronic HCV infection 13 .…”
Section: Groupsmentioning
confidence: 99%